Use of dental care services among adolescents living with HIV on antiretroviral treatment in Kampala, Uganda: a cross-sectional study - Maria Gorretti Nakyonyi; Nancy Birungi; Catherine Lutalo Mwesigwa; Anne Nordrehaug Åstrøm (BMC, 2024)
Abstract Objective The primary purpose of this study was to assess the prevalence and socio-behavioral determinants of ever-use of dental care services among adolescents aged 10-18 years, living with HIV, on Antiretroviral treatment (ART), and attending selected HIV clinics in Kampala, Uganda. Methods A cross-sectional study was carried out between March and September 2020. The study conveniently recruited 154 adolescents between 10 and 18 years old from 4 specific HIV clinics in Kampala. Andersen's behavioral model guided the selection of variables, with the ever-use of dental care services as the outcome and predisposing, enabling, need-related factors and personal dental health practices as exposure variables. Data were analyzed using Fischer's exact test for cross-tabulation and modified Poisson regression for multivariate analysis. Results The prevalence of ever-use of dental care services was 12.3%. The adolescents aged 14-18 had higher odds of using dental care services (Prevalence ratio (PR) of 3.35 than those aged 10-13 years. Fear of the spread of HIV was negatively associated with ever-use of dental care services (PR of 0.06). Participants who were afraid of going to the dentist had higher odds of using dental care services (PR of 2.98) than those not afraid. Failure to receive dental treatment because it was not part of the medical appointment had a positive association with the ever-use of dental care services (PR of 4.50). Those who were satisfied with their dental condition had lower odds of using dental care services. The bad oral odor was positively associated with the ever-use of dental care services (PR of 2.80). The use of soap for toothbrushing was positively associated with the ever-use of dental care services (PR of 2.51). Conclusion The study found a low frequency of dental care use among HIV-infected adolescents in Kampala, Uganda, with age being a predisposing factor. Enabling factors included fear of HIV spread, medical-dental appointment incoordination, and satisfaction with the dental condition and bad oral odor while under personal dental health practices. The use of soap for toothbrushing was an important association with dental care. Nevertheless, these study results cannot be generalized to the entire HIV adolescent population in Uganda.